Time-release versus immediate-release formulations of venlafaxine, paroxetine and bupropion: a comparative study of a nationally representative sample of the US working population. Issue 2 (12th February 2014) - Al-Ruthia, Yazed; Hong, Song Hee
Abstract: Objective: The purpose of this study is to compare patient-reported outcomes (PROs) such as health-related quality of life, mental disorder and psychological distress among users of time-release (TR) versus immediate-release formulations of three commonly prescribed antidepressants in a sample of the US working population. Methods: Adjusted multiple linear and logistic regression analyses using data from 2004 to 2010 Medical Expenditures Panel Surveys were conducted. The health-related quality of life was measured based on the Physical Component Summary (PCS-12) and the Mental Component Summary (MCS-12) of the SF-12v2. The mental disorder and the psychological distress were measured by the Patient Health Questionniare-2 and the Kessler 6 respectively. Key findings: The utilization of TR formulations was not associated with higher scores in the SF12-v2, (β = −0.546, P = 0.442) and (β = −0.806, P = 0.346) for both PCS-12 and MCS-12 respectively. The users of TR formulations did not significantly differ in their likelihood of having a score of ≥3 in the Patient Health Questionniare-2 (OR = 1.048, P = 0.677). Furthermore, the utilization of TR formulations was not associated with lower scores in the Kessler 6 Scale (β = 0.073, P = 0.846). Conclusions: Although controlled clinical trials report favourable tolerability profiles for TR formulations, it still remains unclear whether these formulations lead to better PROs in real-world patient-care settings.